GERAKAN PEDULI LINGKUNGAN MELALUI BANK SAMPAH TINGKAT SEKOLAH DASAR DI KOTA GORONTALO - Dwi Nur Handayani; Alfiyah Agussalim (Universitas Bina Taruna Gorontalo, 2022)
Implementing community service activities in the form of environmental care movements through elementary school level waste banks is an effort to change waste processing behavior for the better and is instilled from an early age in elementary school students. Good school environmental conditions aim to create a conducive place for learning activities and increase the awareness of school residents to take responsibility for efforts to save the environment. Forming environmentally caring behavior from an early age can be done through the development of school waste banks. However, the waste bank at SDN 39 Hulontalangi has not developed optimally as seen from the school community's ability to sort waste which is still lacking, knowledge about the use and processing of waste based on type is not yet understood by the school community. Apart from that, another problem with the school's less than optimal waste bank is limited knowledge and the management's human resource skills as well as marketing management resulting from the creativity of partner schools that do not yet exist. Based on the existing problems, the approach used in implementing activities uses an empowerment model through preparation, FGD, training and mentoring stages. The expected output of this program is to increase the school community's knowledge regarding school waste bank management and understanding of various types of waste, both organic and inorganic waste, as well as increasing the school community's creativity in recycling waste so that there is a paradigm shift regarding waste when managed. can provide economic value.